Radiation-hygienic passportization and USIDC-information basis for management decision making for radiation safety of the population of the Russian Federation Report 2: Characteristics of the sources and exposure doses of the population of the RF - G. G. Onishchenko; A. Yu. Popova; I. К. Romanovich; A. N. Barkovsky; T. A. Kormanovskaya; I. G. Shevkun (Радиационная гигиена)
This article presents a description of the sources of ionizing radiation and annual doses to the population as a whole for the Russian Federation and separately for the subjects, as well as for the most exposed population groups. The average individual effective annual dose of Group A personnel in 2016 was 1.2 mSv, or 6.0% of the average annual dose limit of 20 mSv. During the period from 1998 to 2005, the average annual individual doses of the personnel of Group A gradually decreased from 2.9 mSv to 1.4 mSv and then stabilized at a level of 1.2–1.4 mSv. The average per inhabitant of the Russian Federation annual effective dose due to natural sources, according to data for 1998-2016, is 3.33 mSv/year, for the Altai Republic – 8.97 mSv/ year, and for some of the most exposed population groups – 3-60 and more mSv/year. Radon exposure makes up the largest fraction (59.50%) of radiation dose due to natural sources. The average per inhabitant of the Russian Federation annual effective dose due to medical exposure in 2016 was 0.51 mSv/year, and after some stabilization in 2013-2015 at a level of 0.45-0.48 mSv/year, there was a tendency to increase. The average annual effective dose of the Russian Federation citizens from all sources of ionizing radiation is 3.76 mSv/year. The highest value of this quantity in 2016 took place in the Republics of Altai (7.2 mSv), Tyva (5.7 mSv), Adygea (5.6 mSv), the Irkutsk region (5.7 mSv) and in the Jewish Autonomous Oblast (6.6 mSv). Natural sources of radiation in the Russian Federation determine 86.1% of the collective radiation dose of the population, medical exposure – 13.6%. In general, the radiation situation in the Russian Federation remains stable over the last decades and in the prevailing territory can be characterized as satisfactory, with the exception of territories affected as a result of the past radiation accidents (Chelyabinsk region, southwestern districts of the Bryansk region) and some settlements in those subjects of the Russian Federation, where exposure of significant populations due to natural sources of ionizing radiation exceeds 10 mSv / year.